Dermoid Cyst of the Retrouterine Pouch of Douglas - Heng-Ju Chen; Bih-Chwen Hsieh; Hun-Shan Pan; Kok-Min Seow; Yieh-Loong Tsai; Jiann-Loung Hwang (Elsevier, 2004)
Objective: Benign cystic teratomas are one of the most common ovarian tumors. Teratomas of the retrouterine pouch of Douglas are extremely rare. We report a case of benign cystic teratoma of the Douglas pouch in a woman who underwent laparoscopic surgery. Case Report: A 61-year-old woman presented with lower abdominal pain. On pelvic examination, a pelvic mass was palpated in the right adnexa. Transvaginal ultrasound demonstrated two cyst-like masses in the right adnexa. One was homogeneous and measured 4.0 × 3.5 cm, while the other was heterogeneous and measured 3.5 × 3.0 cm. The concentration of the CA125 tumor marker was 8.88 U/mL. On laparoscopy, a cyst 5 × 4 cm in diameter located in the right adnexa, and a 4 × 3 cm well-circumscribed tumor in the cul-de-sac were found. Pathology revealed a right ovarian simple cyst and a benign cystic teratoma in the pouch of Douglas. Conclusion: The etiology of benign cystic teratomas of the Douglas pouch is poorly understood. We report a rare site of a benign cystic teratoma that may provide insights into the differential diagnosis of a pelvic mass in the retrouterine pouch of Douglas.